A Study on the Implication of Tourism Destination and Customer Satisfaction-Based Sustainable Cultural and Heritage Tourism on Tourists Retention in Nias Island-Indonesia - LAOLI, Victorinus; HULU, Fatolosa; NAZARA, Desman Serius; BAENE, Eduar; WARUWU, Sukaaro; MENDROFA, Yupiter (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).02, 2019)
Cultural and heritage tourism is a form of tourism that merges elements of education, tour, cultural and nature preservation as well as economic activities. Since local culture in its original context is the main attractions, then the potential of local culture to disappear can be resolved. Based on the research results on the effect of Sustainable cultural and heritage tourism on tourist’s retention, it was discovered that there is an increase in the effect of Sustainable cultural and heritage tourism on tourist’s retention. Based on the findings of this research regarding the effect of Tourism Destination on tourist’s retention, it was discovered that there is an effect of Tourism Destination on tourist’s retention. With the improvement of Tourism Destination, tourist’s retention can be increased. Based on findings of this research, it was discovered that tourist satisfaction has no effect on tourist’s retention. The decreased Tourist Satisfaction leads to the decline in tourist’s retention. Regarding the effect of sustainable cultural and heritage tourism, tourism destination and customer satisfaction on tourist’s retention in Nias Island, it was revealed that these three variables (sustainable cultural and heritage tourism, tourism destination and customer satisfaction) have simultaneous effects on tourist’s retention in Nias Island.